Performance Audit on Implementation of Mid Day Meal Scheme (2009-2014) - CAG of India (CAG of India)
The National Programme of Nutritional Support to Primary Education (Mid Day Meal Scheme) was launched in August 1995 to boost universalisation of primary education by increasing enrolment, retention and attendance simultaneously impacting on the nutrition levels of children. The scheme lays emphasis on providing cooked meals with minimum 300 calories and 8-12 grams of proteins and adequate quantities of micronutrients. The scheme was extended to children studying in upper primary classes from 2008-09. The scheme was earlier reviewed by us in 2007 and the results were included in the CAG’s Audit Report No. 13 of 2008 tabled in Parliament in October 2008. The Public Accounts Committee (15th Lok Sabha), in its Ninth Report (subsequently, 28th Report) on CAG’s Report No. 13 of 2008 of Mid Day Meal Scheme (MDM Scheme) had made a number of recommendations. The current audit inter-alia looked into whether the Government has taken appropriate actions on the recommendations. Important findings of this Performance Audit Report are given below: The enrolment of children in the MDM Scheme covered schools registered a consistent decline over the years from 14.69 crore children in 2009-10 to 13.87 crore children in 2013-14. In contrast, the enrolment of children in private schools witnessed an increase of 38 per cent from ₹ 4.02 crore to ₹ 5.53 crore during the same period indicating that Mid Day Meal (MDM) in itself was not a sufficient condition to retain children in schools, and that here is a growing section of society seeking better quality in education. (Para No. 2.2) It is time to realise that providing meal is a means to an end, serving the larger purpose of education. Clear trends were noticed, which demonstrated that the meal served its purpose only when the expectations of parents, with respect to good education for their wards, was fulfilled. (Para No. 2.2)
For the Period 2009-2014